Impacts of cigarette smoking on liver fibrosis and its regression under therapy in male patients with chronic hepatitis B. (15th April 2019) - Xiong, Ming; Li, Junying; Yang, Shuling; Zeng, Fansen; Ji, Yali; Liu, Jiang; Wu, Qiaoping; He, Qingjun; Tang, Xiaoting; Jiang, Ronglong; Zhou, Fuyuan; Chen, Yongpeng; et al.
Abstract: Background & Aims: The role of cigarette smoking in the development of chronic hepatitis B (CHB) remains poorly understood. We assessed the potential contributions of cigarette smoking to liver fibrosis and its regression after starting antiviral therapy in CHB patients. Methods: In this cohort study, 2144 consecutive male CHB patients under no antiviral therapy were evaluated and 206 patients with significant liver fibrosis (≥F2) initiating antiviral therapy had longitudinal follow‐up. Liver fibrosis was measured by liver stiffness measurement using transient elastography. To adjust for imbalances between smoking history and never smoking groups, propensity score (PS) matching model with 1:1 ratios were performed. Cigarette smoking history and intensity (pack‐years) were collected and documented using a standardized questionnaire. Results: Before PS matching, 432/2144 patients had advanced fibrosis in prevalence cohort. Patients with smoking history (n = 1002) had a greater prevalence of advanced fibrosis than those without (n = 1142) (24.4% vs 16.5%, P  = 0.001). Multivariate logistic regression analysis demonstrated that smoking contributed to advanced fibrosis (OR, 1.458; 95% CI, 1.114‐1.908). In longitudinal cohort, multivariate logistic regression analysis demonstrated retarded fibrosis regression in patients with history of smoking ≥10 pack‐years (OR, 0.288; 95% CI, 0.1‐0.825). After PS matching, patients with smoking history had higher prevalence of advanced fibrosis (22.8% vs 18%, P  = 0.024) than those non‐smokers. In post‐PS‐matching logistic regression, the effect of smoking on advanced fibrosis persisted (OR, 1.415; 95% CI, 1.047‐1.912; P  = 0.024). Conclusions: Cigarette smoking in male CHB patients aggravated liver fibrosis prior to and delayed fibrosis regression under antiviral therapy.